2014
DOI: 10.1007/s40789-014-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the fractal theory for evaluating effects of coal comminution by waterjet

Abstract: Comminution of coal to ultrafine sizes by high-pressure waterjet provides a novel method for preparation of coal-water fuels for next generation, near-zero emission electric power generation. The particle size distribution (PSD) of ground coal is a key parameter in the preparation of slurries as it determines the settling behavior of the particles and viscosity of the coal-water mixture. There are several methods available for representation and evaluation of particle size analysis data. However, fractal theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The analyzed subsequent designs included equipment for ultra-pure coal micronization with the use of a high-pressure water jet [33] and of coal-water slurry flowing through a labyrinthshaped comminuting channel [34]. The review also covered other coal micronization devices [6,35], as well as a test rig developed for investigating cavitation-supported hydrojet comminution of coal for the production of ultrafine coal particles [36,37], together with its technical characteristics presented in [38]. Consideration was also given to [39], which offers a detailed and comprehensive description of the methods for the fabrication and processing of various fine particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyzed subsequent designs included equipment for ultra-pure coal micronization with the use of a high-pressure water jet [33] and of coal-water slurry flowing through a labyrinthshaped comminuting channel [34]. The review also covered other coal micronization devices [6,35], as well as a test rig developed for investigating cavitation-supported hydrojet comminution of coal for the production of ultrafine coal particles [36,37], together with its technical characteristics presented in [38]. Consideration was also given to [39], which offers a detailed and comprehensive description of the methods for the fabrication and processing of various fine particles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the tests showed a limited usefulness of ultrasound treatment for coal comminution in an aqueous environment [42]. Still, the usefulness of a fractal model to characterize the degree of the particle size distribution of coal [37] comminuted in a hydro-jet mill was positively evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang et al adopted the single power law fractal dimension to evaluate the PSD and compactability of coal gangues. Li et al characterized the PSD of coal through a volume-based fractal model and found a bifractal performance of coal particles. Moreover, the effects of coal water slurry particle size on the rheological behavior and combustion dynamics have been characterized by the fractal theory .…”
Section: Introductionmentioning
confidence: 99%